Autologous platelet lysate and mononuclear stem cell of chronic periodontitis. Case presentation. - Amparo Pérez-Borrego; Georgina Hernández-Aréchaga; Norma Fernández Delgado; Ana Iris González-Iglesias (Universidad de Ciencias Médicas de La Habana, 2017)
Introduction: Treatment of chronic periodontitis is prolonged by persistent inflammation in affected tissues. Regenerative medicine shows encouraging results. It is the first time in Cuba, according to the reviewed literature, that the combination of platelet lysate and autologous mononuclear cells is used in this treatment. Objective: to show the effect of the combination of platelet lysate and autologous mononuclear cells in the treatment of periodontitis. Presentation of the case:  A 44-year-old female patient diagnosed with periodontitis who had been treated for 1 year without surgical procedures due to persistent inflammation. She is referred to the periodontics consultation of the "Dr. Enrique Cabrera" General Hospital to receive treatment with regenerative medicine. Treatment with autologous platelet lysate was considered, once the scaling and root planer had been completed, the affected gingivae were prefixed with the platelet lysate. At 7 days after the lysate is applied, the gingiva shows no clinical signs of inflammation, and a noticeable reduction in the number of affected teeth and the depth or elimination of periodontal pockets and tooth mobility. Bone defects with a mononuclear cell implant were surgically treated one month later. When evaluating at 6 months, radiographic signs of trabecular organization, definition of the cortical bone, and bone formation in the area of bone defects were found variably. Conclusions: The combined treatment of autologous platelet lysate and mononuclear cells shows a satisfactory evaluation in the treatment of chronic periodontitis and reduces treatment time. Keywords: Regenerative medicine, autologous platelet lysate, chronic periodontitis, autologous mononuclear stem cell